Analisis Hubungan antara Imunisasi BCG dan Kejadian Tuberkolosis pada Anak Usia 1-4 Tahun dengan Metode Purposive Sampling: Analysis of the Relationship between BCG Immunization and the Incidence of Tuberculosis in Children Aged 1-4 Years Using the Purposive Sampling Method - Susilowati, Lilik; Sulastriningsih, Kursih; Nurlelawati, Ella; Rosmiati (Technomedia Journal, 2024)
BCG immunization is the first step in preventing tuberculosis (TB) caused by Mycobacterium tuberculosis. This disease is potentially fatal and requires vigilance from parents because babies are susceptible to TB infection. This study aims to evaluate the factors that influence BCG immunization and the incidence of TB in children aged 1-4 years at the Batauga Community Health Center, South Buton Regency, during January to June 2023. Conducted in July 2023, this research involved 209 children as a population, with 68 of them being the sample. The results of the study showed that there was a relationship between knowledge, attitudes and anxiety with BCG immunization status and the incidence of TB in children under five, indicated by relevant statistical significance (ρ < α=0.05). These findings highlight the importance of education and attitude change in increasing BCG immunization and reducing the risk of TB in children under five. In this context, preventive efforts that focus on health education and public understanding of the importance of BCG immunization can play a vital role in controlling the spread of TB in the community.